The politics of IMF forecasts - Axel Dreher; Silvia Marchesi; James Raymond Vreeland (ETH Zurich, KOF Swiss Economic Institute, 2007)
Using panel data for 157 countries over the period 1999-2005 we empirically investigate the politics involved in IMF economic forecasts. We find a systematic bias in growth and inflation forecasts. Our results indicate that countries voting in line with the US in the UN General Assembly receive lower inflation forecasts. As the US is the Fund's major shareholder, this result supports the hypothesis that the Fund's forecasts are not purely based on economic considerations. We further find inflation forecasts are systematically biased downwards for countries with greater IMF loans outstanding relative to GDP, indicating that the IMF engages in defensive forecasting. Countries with a fixed exchange rate regime also receive low inflation forecasts. Considering the detrimental effects that inflation can have under such an exchange rate regime, we consider this evidence consistent with the Fund's desire to preserve economic stability.
Keywords: C23; D72; F33; F34; 330; IMF; Economic Forecasts; Political Influence; Wirtschaftsprognose; Internationale Wirtschaftsorganisation; Prognoseverfahren; Bias; Ideologie; Welt